HIV Controllers Exhibit Effective CD8 + T Cell Recognition of HIV-1-Infected Non-activated CD4 + T Cells (2019)
Even with sustained antiretroviral therapy, resting CD4 + T cells remain a persistent reservoir of HIV infection, representing a critical barrier to curing HIV. Here, we demonstrate that CD8 + T cells recognize infected, non-activated CD4 + T cells in the absence of de novo protein production, as measured by immune synapse formation, degranulation, cytokine production, and killing of infected cells. Immune recognition is induced by HLA-I presentation of peptides derived from incoming viral particles, and recognition occurred either following cell-free virus infection or following cell-to-cell spread. CD8 + T cells from HIV controllers mediate more effective immune recognition than CD8 + T cells from progressors. These results indicate that non-activated HIV-infected CD4 + T cells can be targeted by CD8 + T cells directly after HIV entry, before reverse transcription, and thus before the establishment of latency, and suggest a mechanism whereby the immune response may reduce the size of the HIV reservoir. The cure for HIV is not achievable due to HIV reservoirs, mostly in resting CD4 + T cells. Monel et al. show that CD8 + T cells from HIV controllers are able to establish immunological synapses with HIV + resting CD4 + T cells, leading to IFN-?, MIP1-? production, degranulation, and the elimination of the target cells. © 2019 The Authors